Psychometric properties of the Finnish version of the Women's Health Questionnaire - Katainen RE; Engblom JR; Vahlberg TJ; Polo-Kantola P (LIPPINCOTT WILLIAMS & WILKINS, 2022)
Objective: The Women's Health Questionnaire (WHQ) is a validated and commonly used instrument for measuring climacteric-related symptoms. A revised version was previously developed. However, validation in a Finnish population is lacking. As it is important to use qualified instruments, we performed a validation study of the WHQ in a Finnish population.Methods: In all, 3,421 women, aged 41 to 54 years, formed the study population. In the original 36-item WHQ, the items were rated on a 1 to 4 scale and on a binary scale (0-1). The scaling of the revised 23-item WHQ was 0 to 100. We evaluated the psychometric properties (internal consistency, correlations between the symptom domains, factor structure, and sampling adequacy) in all three versions.Results: For the 1 to 4 scale and on the revised version of the WHQ, the internal consistency was acceptable (the Cronbach's alpha coefficients > 0.70) for most of the domains. On the binary scale, the majority of the coefficient values were below the acceptable level. The original symptom domains, especially those on the revised version, were recognizable from the factors in the exploratory factor analysis, but there were some limitations. The Kaiser-Meyer-Olkin values were high.Conclusions: The WHQ is a valid instrument for measuring climacteric-related symptoms in Finnish middle-aged women. The psychometric properties of the revised 23-item WHQ were as good or even better than those of the original 36-item WHQ. Thus, we encourage use of the revised version.